Protective effect of bronchial challenge with hypertonic saline on nocturnal asthma - M.C. Borges; E. Ferraz; J. Terra-Filho; E.O. Vianna (Brazilian Journal of Medical and Biological Research, 2008)
Inhalation of hypertonic saline (HS) causes bronchoconstriction in asthmatic subjects. Repeated inhalation of HS leads to substantially reduced bronchoconstriction, known as the refractory period. Refractoriness due to different stimuli has also been described (cross-refractoriness). Nocturnal asthma is defined as an increase in symptoms, need for medication, airway responsiveness, and/or worsening of lung function that usually occurs from 4 to 6 am. Our objective was to determine the effect of refractoriness on nocturnal asthma. The challenge test consisted of inhalations of 4.5% saline with increasing durations until a reduction of 20% in forced expiratory volume in 1 s (FEV1) (PD20HS) or total time of 15.5 min. Twelve subjects with nocturnal asthma were challenged with HS at 16:00 and 18:00 h and FEV1 was measured at 4:00 h. One to 2 weeks later, FEV1 was determined at 16:00 and 4:00 h. LogPD20HS at 18:00 h was significantly greater than logPD20HS at 16:00 h, 0.51 ± 0.50 and 0.69 ± 0.60 mg, respectively (P = 0.0033). When subjects underwent two HS challenges in the afternoon, mean (± SD) FEV1 reduction was 206 ± 414 mL or 9.81 ± 17.42%. On the control day (without challenge in the afternoon) FEV1 reduction was 523 ± 308 mL or 22.75 ± 15.40% (P = 0.021). Baseline FEV1 values did not differ significantly between the control and study days, 2.48 ± 0.62 and 2.36 ± 0.46 L, respectively. The refractory period following HS challenges reduces the nocturnal worsening of asthma. This new concept may provide beneficial applications to asthmatic patients.